Giant vesicle calculi leading to spontaneous bladder rupture and acute renal failure: an unusual presentation. (25th October 2018) - Sharma, Deepanshu; Garg, Gaurav; Pandey, Siddharth; Goel, Apul
Abstract : Spontaneous rupture of the urinary bladder is extremely rare. We report a case of a 70-year-old man with spontaneous bladder rupture secondary to neglected giant vesicle calculi who presented as acute renal failure. The patient was stabilised with per-urethral catheterisation and extravesical drain placement. About 700 mL pus mixed with urine was drained through the per-urethral catheter and approximately 2000 mL of pus was drained through the extravesical drain. Cystolithotomy showed two large calculi which were removed.